Towards a Cure for Diamond-Blackfan Anemia: Views on Gene Therapy - Vale, Matilde; Prochazka, Jan; Sedlacek, Radislav (Cells, 2024)
Diamond-Blackfan anemia (DBA) is a rare genetic disorder affecting the bone marrow's ability to produce red blood cells, leading to severe anemia and various physical abnormalities. Approximately 75% of DBA cases involve heterozygous mutations in ribosomal protein (RP) genes, classifying it as a ribosomopathy, with RPS19 being the most frequently mutated gene. Non-RP mutations, such as in GATA1, have also been identified. Current treatments include glucocorticosteroids, blood transfusions, and hematopoietic stem cell transplantation (HSCT), with HSCT being the only curative option, albeit with challenges like donor availability and immunological complications. Gene therapy, particularly using lentiviral vectors and CRISPR/Cas9 technology, emerges as a promising alternative. This review explores the potential of gene therapy, focusing on lentiviral vectors and CRISPR/Cas9 technology in combination with non-integrating lentiviral vectors, as a curative solution for DBA. It highlights the transformative advancements in the treatment landscape of DBA, offering hope for individuals affected by this condition.
Keywords: CRISPR-Cas Systems; Diamondova-Blackfanova anemie; Ribosomal Proteins; Genetic Therapy; editace genu; Anemia, Diamond-Blackfan; CRISPR-Cas systémy; ribozomální proteiny; genetická terapie; mutace; Gene Editing; genetické vektory; Lentivirus; Genetic Vectors; Mutation; zvířata; Humans; lidé; Animals